2016
DOI: 10.1146/annurev-phyto-080615-100140
|View full text |Cite
|
Sign up to set email alerts
|

Root Border Cells and Their Role in Plant Defense

Abstract: Root border cells separate from plant root tips and disperse into the soil environment. In most species, each root tip can produce thousands of metabolically active cells daily, with specialized patterns of gene expression. Their function has been an enduring mystery. Recent studies suggest that border cells operate in a manner similar to mammalian neutrophils: Both cell types export a complex of extracellular DNA (exDNA) and antimicrobial proteins that neutralize threats by trapping pathogens and thereby prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 117 publications
0
97
0
1
Order By: Relevance
“…We also considered other approaches, such as the use of RNAi to silence components of flavonoid exudation machinery and the use of adsorbents to prevent rhizodeposit isoflavonoids from reaching rhizosphere microbes. However, rhizodeposition of isoflavonoids occurs through mechanisms other than root exudation as well, e.g., root border cells (Hawes et al 2000). Therefore, silencing components of root exudation machinery (e.g., ABC transporters [Brechenmacher et al 2009;Sugiyama et al 2007]) might not result in efficient depletion of isoflavonoids in rhizodeposits.…”
Section: Discussionmentioning
confidence: 99%
“…We also considered other approaches, such as the use of RNAi to silence components of flavonoid exudation machinery and the use of adsorbents to prevent rhizodeposit isoflavonoids from reaching rhizosphere microbes. However, rhizodeposition of isoflavonoids occurs through mechanisms other than root exudation as well, e.g., root border cells (Hawes et al 2000). Therefore, silencing components of root exudation machinery (e.g., ABC transporters [Brechenmacher et al 2009;Sugiyama et al 2007]) might not result in efficient depletion of isoflavonoids in rhizodeposits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, crop species had a greater influence on the rhizosphere than model plants, selecting more rhizosphere-specific bacterial OTUs (Supplementary Figures S2k, S5c and S11). This is probably explained by the more extensive root systems of crop plants, leading to increased root exudation and root turnover (Hawes et al, 2000).…”
Section: Microbiota Selection In Compostmentioning
confidence: 99%
“…Detaching root cap cells are termed border cells (BCs), because they constitute the border between the root and the soil environment. It has been suggested that BCs mediate plant-rhizosphere interactions by adjusting the physical and chemical properties of the soil and by influencing the microbial flora around the roots (Cannesan et al, 2012;Driouich et al, 2013;Hawes et al, 2000;Vicre et al, 2005). In Arabidopsis, BCs do not detach as individual cells, but rather separate as an organized layer.…”
Section: Introductionmentioning
confidence: 99%